Consumer Behavior and Sustainability in E-Commerce: a Bibliometric Analysis to Exploring the Global Trends Research - Khoerunnisa; Naghmah Faadiyah; Ilham Malik Fajar; Shela Virgin Agitya Maharani (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Sustainable consumption is related to the increase in consumer behavior, especially online purchases. Sustainability regarding e-commerce research such as research status, development, and structure of consumer behavior is still rare despite the increasing interest in this topic. The purpose of this study is to analyze the conceptual, social and dynamic knowledge about consumer behavior and sustainability in e-commerce research. Bibliometric analysis was conducted as well as data collection from 297 articles from the Scopus database. The research resulted in a close relationship between these topics and, big data analytics, customer engagement, online services, sales, sustainable development and supply chain management indicating different research approaches and cross-cutting themes related to these topics. Identifying these research trends contributes to academic sustainability research and suggests future research topics. Keywords: consumer behavior; sustainability; e-commerce; bibliometric